Banach Manifolds with Bounded Structure and the Gauss?Ostrogradskii Formula - Bogdanskii, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We propose a version of the Gauss - Ostrogradskii formula for a Banach manifold with uniform atlas.